2017
DOI: 10.1523/jneurosci.3196-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of NMDA Receptor-Mediated Transmission by SK Channels Underlies Dorsal-Ventral Differences in Dynamics of Schaffer Collateral Synaptic Function

Abstract: Behavioral, physiological, and anatomical evidence indicates that the dorsal and ventral zones of the hippocampus have distinct roles in cognition. How the unique functions of these zones might depend on differences in synaptic and neuronal function arising from the strikingly different gene expression profiles exhibited by dorsal and ventral CA1 pyramidal cells is unclear. To begin to address this question, we investigated the mechanisms underlying differences in synaptic transmission and plasticity at dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 67 publications
3
52
1
6
Order By: Relevance
“…In agreement with this suggestion, a recent study showed that pyramidal neurons of the ventral CA1 region express significantly higher levels of Ca 2+ ‐activated SK‐type K + channels. These, in turn, were shown to inhibit NMDAR‐dependent EPSP amplification to a greater degree in the ventral as opposed to the DH (Babiec, Jami, Guglietta, Chen, & O'Dell, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this suggestion, a recent study showed that pyramidal neurons of the ventral CA1 region express significantly higher levels of Ca 2+ ‐activated SK‐type K + channels. These, in turn, were shown to inhibit NMDAR‐dependent EPSP amplification to a greater degree in the ventral as opposed to the DH (Babiec, Jami, Guglietta, Chen, & O'Dell, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although GluN2A expression was equivalent across the dorsal, intermediate and ventral CA1 regions, the graded expression of GluN2B‐containing NMDARs can be expected to impact on LTP responses, as it will serve to alter the GluNA/GluN2B ratios across the dorsoventral axis. Additionally, an enhanced SK‐type K+ channel‐dependent suppression of NMDAR activation in ventral CA1 pyramidal cells, as opposed to dorsal CA1 pyramidal cells (Babiec et al, ), would be expected to escalate the propensity differences of hippocampal parts in expressing long‐term synaptic potentiation. LTP maintenance is supported by mGlu5 (Mukherjee and Manahan‐Vaughan, ) and this receptor also potentiates NMDAR currents (Doherty, Palmer, Henley, Collingridge, & Jane, ; Perroy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…LTP is a basic synaptic model of learning and memory (Martin and Morris, ) and it is typically induced at hippocampal synapses (Bliss, Collingridge, & Morris, ). The ability of hippocampal synapses for LTP, however, is not evenly distributed along the dorsoventral axis of the hippocampus (Babiec, Jami, Guglietta, Chen, & O'Dell, ; Colgin, Kubota, Jia, Rex, & Lynch, ; Grigoryan, Korkotian, & Segal, ; Kouvaros and Papatheodoropoulos, ; Maruki, Izaki, Nomura, & Yamauchi, ; Milior et al, ; Moschovos, Kostopoulos, & Papatheodoropoulos, ; Papatheodoropoulos and Kostopoulos, ; Schreurs, Sabanov, & Balschun, ). On the contrary, the difference in LTP emblematically represents the recently emerging concept of intrinsic diversification along the dorsoventral axis of the hippocampus, recently reviewed in (Papatheodoropoulos, ; Tushev and Schuman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, SK channel expression is higher in the vHC than the dHC and these channels buffer glutamatergic synaptic activity to a greater extent in the vHC (Babiec et al, 2017). This differential distribution of SK channels may partly explain the differential effects of CIE on synaptic transmission along the dorsal-ventral axis of the hippocampus While CIE is a well-validated rodent model of AUD, there are many parallels between the maladaptive behavioral phenotypes promoted by this model and models of stress (Holmes et al, 2012;Morales et al, 2018Morales et al, , 2015.…”
Section: Discussionmentioning
confidence: 97%